ASSESSING THE EFFECTIVENESS OF SELF-HELP GROUP IN ALAPPUZHA - P T, Renjumol (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Self-Helping Groups play a vital role in the upliftment of the rural population and plays a prominent role in poverty alleviation. Especially in Kerala, the Kudumbashree scheme introduced by the Kerala government with the slogan “Reaching out to families through women and reaching out to the community through families” is playing a dynamic role in the upliftment of socially and economically backward communities. In this quantitative study, we evaluate the performance of the self-help groups in the Alappuzha district by collecting the required data from 50 active beneficiaries of the 10 Kudumbashree units using a self-made questionnaire. The study corroborates that the Kudumbashree mission is one of the most effective schemes for the upliftment of rural masses especially women micro-entrepreneurs.